State and the statecract of the centrals of government Mataram Islam Kingdom in Java - HY Agus Murdiyastomo (Universitas Negeri Yogyakarta, 2016)
This study is aimed to examine the dynamic of Islamic Mataram kingdom, focusing more on administrative system in Islam Mataram. This research used the five stages historical research method according to Kuntowijoyo, which are topic selection, heuristic, verification, interpretation and writing. Panembahan Senopati defeated Pajang and built a palace in Kotagede which later was used by Mataram kings until their peak of glory under Sultan AgungHanyakrakusuma. However the defeat of Mataram from VOC caused them to lose their ground, moreover after Sultan AgungHanyakrakusuma deceased. His successor, Amangkurat I think that Kotagede as the central of economic activities considered to be no longer suitable for the central of government. Therefore he ordered to move the palace from Kotagede to Pleret. Raden Mas Rahmat, as ‘Amangkurat II’, didn’t want to go back to Pleret because it had been taken by Puger Prince, and then built new palace in Kartasura. Amangkurat III escaped to the east when Kartasura was taken. But this palace would also be abandoned later, and moved to Surakarta when Pakubuwono II ruled the place. Mataram moved its government four times, from Kotagede, Plered, Kartasura, and lastly, Surakarta.Keywords: government, Islamic Mataram.